Junction Temperature Prediction for LED Luminaires Based on a Subsystem-Separated Thermal Modeling Method - Miao Cai; Zhi Liang; Kun-Miao Tian; Ming-Hui Yun; Ping Zhang; Dao-Guo Yang; Guo-Qi Zhang (IEEE Access, 2019)
The junction temperature (Tj) of LEDs in an LED luminaire is useful for projecting the luminous flux maintenance or lifetime of luminaires. Normally, a LED luminaire has a unique and complex geometric outline, and its LED package size is only a few millimeters. The thermal modeling procedure with one luminaire model is complex. Achieving a precise Tj of luminaires quickly in modeling is still a great challenge. In this work, aiming at providing a simple modeling method to predict a precise luminaire Tj, a subsystem-separated thermal modeling method for luminaires is proposed by following the existing form of multi-domain modeling. The detailed package model is linked with the luminaire model, while the average temperature at the bottom surface of the LED package is associated with an assumed equivalent convective heat transfer coefficient (ECHTC) at the package model. An adequately assumed ECHTC is obtained, while a unique average temperature is achieved from the luminaire model. Results show that a precise luminaire Tj is projected rapidly by modeling the package model with the adequate ECHTC and a proposed power law equation. The proposed modeling method not only provides a precise Tj prediction with a small error but also effectively simplifies the modeling of LED luminaires.